Mechanically stable antimicrobial chitosan-PVA-silver nanocomposite coatings deposited on titanium implants - Mishra, Sandeep K.
Bionanocomposite coatings with antimicrobial activity comprising polyvinyl alcohol (PVA)-capped silver nanoparticles embedded in chitosan (CS) matrix were developed by a green soft chemistry synthesis route. Colloidal sols of PVA-capped silver nanoparticles (AgNPs) were synthesized by microwave irradiating an aqueous solution comprising silver nitrate and PVA. The bionanocomposites were prepared by adding an aqueous solution of chitosan to the synthesized PVA-capped AgNPs sols in appropriate ratios. Uniform bionanocomposite coatings with different contents of PVA-capped AgNPs were deposited onto titanium substrates by \"spread casting\" followed by solvent evaporation. Nanoindentation and antimicrobial activity tests performed on CS and bionanocomposites revealed that the incorporation of PVA-capped AgNPs enhanced the overall functional properties of the coatings, namely their mechanical stability and bactericidal activity against Escherichia coli and Staphylococcus aureus. The coated specimens maintained their antimicrobial activity for 8 h due to the slow sustained release of silver ions. The overall benefits for the relevant functional properties of the coatings were shown increase with increasing contents of PVA-capped AgNPs in the bionanocomposites. (C) 2015 Elsevier Ltd. All rights reserved.